(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article provides a historical analysis of the emergence and development of tutor support in foreign countries and in Russia. It reconstructs the evolution of tutorship as a pedagogical phenomenon, identifies the prerequisites for its establishment, and determines its relevance in contemporary educational practice. The study also highlights the content and specific features of tutors’ professional activity in different historical periods.